Efeito da experiência do consumidor de varejo Omnichannel no boca a boca Off-line e Online - Maschio, Hélio Augusto (2022)
A dynamic and competitive scenario has shown itself to retailers. Even they offering an omnichannel format, which seeks to meet the changing needs and preferences of consumers, has been used by companies from different sectors, but there is still the challenge of building meaningful experiences for consumers. Following the stimulus-organism-response (SOR) theoretical approach, using six dimensions (personalization, integration, aesthetics, interaction, customization and privacy/security), and a non-comparative Likert-type scale with seven points (1- I totally disagree to 7 - totally agree), in a deductive hypothetical model via quantitative technique, this study aimed to identify the effects of the omnichannel retail consumer experience on traditional (offline) and digital (online) word-of-mouth. 215 omnichannel retail consumers participated this research, whose responses were obtained through an electronic form. The collected data were analyzed using structural equation modeling. The results indicate that interaction is the dimension with the greatest positive effect on the omnichannel retail consumer experience, and traditional word-of-mouth (offline) overlaps when compared to word-of-mouth (online). In summary, even in an omnichannel retail environment, traditional word-of-mouth predominates, followed by word-of-mouth (social) and word-of-mouth (digital).